2021
DOI: 10.3390/foods10092008
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide Exposure from Common Culinary Preparations in Spain, in Household, Catering and Industrial Settings

Abstract: In 2019, the European Commission recommended monitoring the presence of acrylamide in certain foods not included in Regulation 2158/2017, to consider other sources of exposure to the contaminant. In the present study, eleven groups of processed foods commonly consumed in Spain were classified, according to their food matrix, into potato-based food, cereal-based food and food based on cereal mixed with meat, fish or vegetables. Samples were collected from three different settings: household, catering services a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Therefore, it would be logical to compare the results of muffins with cake. González-Mulero et al ( 40 ) found acrylamide concentration in the range of 15 to 138 μg/kg in sponge cake which was in agreement with the findings in the present study. EFSA reported the set values of acrylamide in cake as 66 μg/kg which were in accordance with the values observed in the samples studied in the present study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it would be logical to compare the results of muffins with cake. González-Mulero et al ( 40 ) found acrylamide concentration in the range of 15 to 138 μg/kg in sponge cake which was in agreement with the findings in the present study. EFSA reported the set values of acrylamide in cake as 66 μg/kg which were in accordance with the values observed in the samples studied in the present study.…”
Section: Resultssupporting
confidence: 93%
“…Fermentation is involved in the preparation of pizza. In a study conducted on pizza by González-Mulero et al ( 40 ), it was found that acrylamide contents were in the range of 15 to 104 μg/kg which was concurrent to the findings of the present study. The acrylamide levels analyzed in pizza samples from Italy were in the range of 90 to 250 μg/kg ( 41 ) which were higher than the values obtained in the present study.…”
Section: Resultssupporting
confidence: 91%
“…Same snacks prepared by different manufacturers contained different acrylamide levels ( 41 ). This is probably due to several factors such as the different types of raw material used or the different heating temperature and time applied during the cooking process.…”
Section: Discussionmentioning
confidence: 99%
“…These items were classified into 6 food groups in a similar way to the Bellicha et al study [ 16 ]: (i) potato fries and chips; (ii) bread; (iii) breakfast cereals; (iv) mixed dishes (pasta, pizza, and croquettes); (v) cookies, pastries, and chocolates; and (vi) coffee. For the determination of the concentration of acrylamide in these 20 acrylamide-containing foods, the quantity of acrylamide for each food was derived from data published using Spanish populations, given the absence of an acrylamide database in this country [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. If no previous Spanish study had evaluated the acrylamide concentration of a particular food, the Scientific Opinion on acrylamide in food of the EFSA was consulted [ 10 ].…”
Section: Methodsmentioning
confidence: 99%